A short update on new approaches to celiac disease - Al Ibrahmi, Btihaj; Bour , Abdellatif (Acta Biomedica Atenei Parmensis, 2022)
Celiac disease is an autoimmune enteropathy of the small intestine, related to gluten intolerance occurring in genetically predisposed patients. Currently, the only available treatment is a lifelong gluten-free diet. However, the total avoidance of gluten is difficult and poses a challenge to patients, nutritionists and treating physicians. For this reason, scientists have developed in recent years new therapeutic approaches complementary to dietary treatment, such as modification of gluten to make gliadin non-toxic, reduction of the inflammatory response with elafin and Lactococcus Lactis, degradation of gluten by endoproteolytic enzymes, and correction of nutritional deficiencies by adding pseudo-cereals to the diet of celiac patients. This literature review focuses on the different treatment strategies for celiac disease previously studied and summarizes the latest advances in this field.